2008
DOI: 10.1002/tox.20304
|View full text |Cite
|
Sign up to set email alerts
|

Combined cytotoxicity and genotoxicity of a marine toxin and seafood contaminant metal ions (chromium and cadmium)

Abstract: Algal bloom with consequent production of marine toxins contaminating bivalves is increasing in costal regions worldwide because of sea water quality worsening. Contamination of seafood by diarrheic shellfish poisoning toxins (DSP) together with metals is frequently reported, a phenomenon not fully explained yet. In this context, metal ions were assayed in clams collected from the banned area of Boughrara, Tunisia, contaminated by Gymnodinium and other algae such as Dinophysis sp, accumulated by these bivalves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The cytotoxic effect of OA has been assessed in a wide variety of cell lines (HepG-2, Glioma cells and Caco-2) after treatment with OA 50 nM during 12 h (Souid-Mensi et al, 2008) and in primary neonatal rat cardiac myocytes after exposure during 18 h to OA 100 nM (Singh et al, 2000). The IC 50 was observed with low nanomolar range of OA: 40 nM in primary cortical cultures (Yi et al, 2005), 27 nM inV79 cells (Rodrigues et al, 2010) and 100 nM in Hela cells (Jayaraj et al, 2009) and U-937 (Ravindran et al, 2011) after 24 h treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxic effect of OA has been assessed in a wide variety of cell lines (HepG-2, Glioma cells and Caco-2) after treatment with OA 50 nM during 12 h (Souid-Mensi et al, 2008) and in primary neonatal rat cardiac myocytes after exposure during 18 h to OA 100 nM (Singh et al, 2000). The IC 50 was observed with low nanomolar range of OA: 40 nM in primary cortical cultures (Yi et al, 2005), 27 nM inV79 cells (Rodrigues et al, 2010) and 100 nM in Hela cells (Jayaraj et al, 2009) and U-937 (Ravindran et al, 2011) after 24 h treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Cyanobacteria are effective biological metal sorbents, representing an important sink for metals in aquatic environment (Cavet et al, 2003;Baptista and Vasconcelos, 2006). Therefore, the studied crude cyanobacterial extracts could contain trace metals, which evoke a variety of acute and chronic toxicity effects including apoptotic changes (Baptista and Vasconcelos, 2006;Palus et al, 2007;Souid-Mensi et al, 2008).…”
Section: Cytotoxicity and Genotoxicity Of Cyanobacterial Extracts Conmentioning
confidence: 99%
“…Although Caco-2 cells originate from the colon, when grown to post-confluency (∼21 days) they spontaneously differentiate and develop morphological characteristics of the small intestine including polarity, intercellular junctions, microvilli, and express markers for mature enterocytes such as brush border hydrolases; as such, Caco-2 are a well-accepted model for studying intestinal absorption, metabolism and cytotoxicity [30], [31], [32], [33], [34], [35]. A previous study reported that chromium (unspecified valence) increased lipid peroxidation in Caco-2 cells [36]. However, to our knowledge, the current study is the first to explore the genotoxicity of Cr(VI) in undifferentiated and differentiated Caco-2, a cell line highly relevant to the intestinal carcinogenicity of ingested Cr(VI).…”
Section: Introductionmentioning
confidence: 99%